Flexible Thin‐Film Electrodes on Porous Polyester Membranes for Wearable Sensors1 . Issue 1 (23rd November 2016) - Gangopadhyay, Aveek; Nablo, Brian J.; Rao, Mulpuri V.; Reyes, Darwin R.
Abstract : Track etching of polymer membranes impart a greater flexibility than their rigid counterparts. Metallic thin‐film electrodes deposited on these porous membranes withstand greater mechanical stress while increasing electrical conductivity, which is enhanced by outward bending. Utilizing these materials as thin‐film electronics opens the possibility of greater advancement in wearables, implantable devices, and biosensors.